The Effect of Economic Development on Illegal Gold Mining in Kuantan Singingi, Indonesia - Trio Saputra; Sulaiman Zuhdi; Fajarwaty Kusumawardhani; Rachmawati Novaria (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: Illegal gold mining activities (PETI) are carried out by the community in the Kuantan Singingi Regency. There are found many mining vessels that can carry out illegal mining activities every day without permission from the local government, which causes a lot of environmental and forest damage. This phenomenon must be controlled by the local government effectively and efficiently. Therefore, community welfare could be achieved based on environmental law. Hence, this study aims to determine the implementation of the prevention policy of illegal gold mining in Kuantan Singingi Regency using a multi-sector organizational network model consisting of a contextual assessment approach, mapping the political economy environment of the network, stakeholder analysis, and joint visioning. This study uses qualitative research approach of research site in kuantan singingi Regency, research informant using purposive sampling technique, research data collection with in-depth interview, observation and documentation of data analysis in this study was conducted using data analysis design according to interactive model. The results showed that stakheolder involved both from government groups and from community groups did not play an active and synergistic role in efforts to control unlicensed gold mining.